Total Phenolics Antioxidant Activity and Phytochemical Profile of Some Plants from the Yotoco National Protected Forest. Valle del Cauca, Colombia - Torres Castañeda, Harlen; Colmenares Dulcey, Ana Julia; Isaza Martínez, José Hipólito (Revista de Ciencias, 2013)
Determining the antioxidant activity and the total phenolic content are routine procedures in most natural product laboratories; however, when dealing with large number of samples, it is necessary to employ methods that allow a quick, easy and economical screening. The aim of this study is to determine the antioxidant activity and the total phenolic content of plant species as criteria for the selection of promising species. To reach this aim, we used twenty species from Yotoco National Protected Forest in Valle del Cauca, Colombia. The species Clidemia tococoidea and Miconia aeruginosa, showed the highest total phenolic content together with the best antioxidant activity in terms of DPPH radical scavenging activity. The excellent correlation (R2=0.9610) shown between these parameters, demonstrated the utility of the process used as a method for primary screening and selection of promising species for phytochemical analysis at a preparative scale for this two assays.